Sistem Informasi Pengelolaan Tugas Akhir Mahasiswa dan Jurnal Penelitian Internal Jurusan Teknik Informatika Politeknik Negeri Ketapang - Eka Wahyudi; Indra Pratiwi (Sekolah Tinggi Teknik - PLN, 2020)
Information system is a matter that must be owned by an agency to be able to support managerial activities and performance in any field. Each agency must have its own information system. The system built in this study is the Final Project Management and Internal Research Journal of the Informatics Engineering Department at the Ketapang State Polytechnic. This analysis is used by collecting data in research. In designing, the authors create a computerized work through the process of designing component models, databases, and user interface components. This system is designed to provide information for students about each Final Project from students of the Informatics Engineering Study Program at the State Polytechnic of Ketapang. Final Project Management can provide services to students. Therefore this study aims to develop IT technology in the Informatics Engineering Department of the Ketapang State Polytechnic. This system was built to facilitate users such as admins and students in managing student final assignments.